The Effectiveness of Cognitive-Behavioral Therapy on Depression, Anxiety, and Quality of Life in Men with Asthma - Moinaldini, Roya; Rafiepoor, Amin; Kordmirza Nikoozadeh, Ezzatollah (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The aim of this study was to examine the effectiveness of cognitive-behavioral therapy (CBT) in reducing symptoms of depression, anxiety, and improving the quality of life in men with asthma.Methods and Materials: This research was conducted using a quasi-experimental method with a pretest-posttest control group design. The statistical sample consisted of 30 men with asthma, who were randomly divided into two equal groups (15 each). The intervention group received cognitive-behavioral therapy, while the control group did not receive any intervention. The tools used in this study included the Beck Depression Inventory (BDI-II), the State-Trait Anxiety Inventory (STAI), and the Asthma Quality of Life Questionnaire (AQLQ). The data were analyzed using repeated measures analysis of variance and SPSS 22 software.Findings: The results indicated that cognitive-behavioral therapy had a significant effect in reducing depression and anxiety and improving the quality of life in the intervention group compared to the control group.Conclusion: These findings confirm the effectiveness of cognitive-behavioral therapy as an effective intervention in improving psychological well-being and enhancing the quality of life in patients with asthma.